What are new treatment concepts in systemic itch?. Issue 12 (9th September 2019) - Kremer, Andreas E.
Abstract: Chronic pruritus is a relevant symptom burden in various systemic diseases. It is most commonly observed in patients with chronic kidney disease, hepatobiliary and hematological disorders as well as adverse drug reaction. Recent basic research has unravelled novel treatment targets which are currently in preclinical phases, clinical trials or have already been licensed. While µ‐opioid receptor antagonists have been used since decades mainly in cholestatic pruritus, the k‐opioid receptor agonist nalfurafine has been licensed in Japan for chronic kidney disease‐associated pruritus (CKDaP) as well as cholestatic pruritus. Further κ‐opioid receptor agonists are currently investigated in various clinical trials including CKDaP. In recent years, the calcium channel blockers gabapentin and pregabalin have also been recognized as effective anti‐pruritus therapy in several internal diseases with the best evidence in chronic kidney disease‐associated pruritus. Neurokinin‐1 receptor antagonists have been investigated with variable benefit in CKDaP, solid tumors and lymphoproliferative disorders such as cutaneous T‐cell lymphoma, Sézary syndrome. Inhibitors of the ileal bile acid transporter (IBAT) represent a selective interruption of the enterohepatic circulation and are currently investigated in various hepatobiliary disorders associated with pruritus. The current development and testing of novel drugs in clinical trials offers hope to struggling physicians and suffering patients.